Comparing Outcomes of Wise-Pattern, Two-Stage Breast Reduction-Reconstruction with and without Acellular Dermal Matrix. Issue 3 (24th August 2021) - Patel, Ashraf A.; Kayaleh, Hana; Sala, Luke A.; Peterson, Dylan J.; Upadhyaya, Prashant K.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Aesthetic results in breast reconstruction for ptotic/obese breasts may be improved when using Wise-pattern closures compared with nipple-sparing mastectomies. In two-stage reconstruction, acellular dermal matrix is commonly used to support the prosthesis. This study tests the efficacy of an alternate technique that uses deepithelialized excess breast skin in lieu of acellular dermal matrix. To better understand whether acellular dermal matrix is necessary, the authors compared postoperative outcomes from reduction-reconstructions that used matrix to those that did not. Methods: The authors retrospectively reviewed the outcomes of patients who underwent staged breast reconstruction following Wise-pattern closures between September of 2016 and October of 2019. Two cohorts were created based on whether acellular dermal matrix was used. Charts were reviewed for incidence of postoperative complications. Results: A total of 164 breasts were reconstructed in 85 female patients. The acellular dermal matrix cohort consisted of 68 breasts, whereas the non–acellular dermal matrix cohort included 96 breasts. After the first stage, the incidence of one or more complications was similar between cohorts (acellular dermal matrix, 32.4 percent; nonmatrix, 35.4 percent; p = 0.684). Minor infection rates were significantly higher in reconstructions using acellular dermal matrix (16.2 percent versus 6.3 percent; p = 0.040). After the second stage, the complication incidence was also similar between cohorts (acellular dermal matrix, 16.2 percent; nonmatrix, 13.5 percent; p = 0.638). Final follow-up time was 445.2 days. Conclusions: Overall complication rates following both stages of reconstruction were similar with and without acellular dermal matrix. When acellular dermal matrix was used, minor infection rates were higher following expander placement. In patients desiring a reduction-reconstruction, the authors find the deepithelialized dermal flap provides ample prosthesis support, without the need for acellular dermal matrix.  CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.